Intestinal secretory mechanisms in Okadaic acid induced diarrhoea. (November 2022) - Costas, Celia; Louzao, M Carmen; Raposo-García, Sandra; Vale, Carmen; Vieytes, Mercedes R.; Botana, Luis M.
Abstract: Okadaic acid (OA) is an important marine lipophilic phycotoxin responsible for diarrhetic shellfish poisoning (DSP). This toxin inhibits protein phosphatases (PPs) like PP2A and PP1, though, this action does not explain OA-induced toxicity and symptoms. Intestinal epithelia comprise the defence barrier against external agents where transport of fluid and electrolytes from and to the lumen is a tightly regulated process. In some intoxications this balance becomes dysregulated appearing diarrhoea. Therefore, we evaluated diarrhoea in orally OA-treated mice as well as in mice pre-treated with several doses of cyproheptadine (CPH) and then treated with OA at different times. We assessed stools electrolytes and ultrastructural alteration of the intestine, particularly evaluating tight and adherens junctions. We detected increased chloride and sodium faecal concentrations in the OA-exposed group, suggesting a secretory diarrhoea. Pre-treatment with CPH maintains chloride concentration in values similar to control mice. Intestinal cytomorphological alterations were observed for OA mice, whereas CPH pre-treatment attenuated OA-induced damage in proximal colon and jejunum at 2 h. Conversely, tight junctions' distance was only affected by OA in jejunum at the moment diarrhoea occurred. In this study we found cellular mechanisms by which OA induced diarrhoea revealing the complex toxicity of this compound. Highlights: Okadaic acid modifies mice stools electrolytes independently from dose. Okadaic acid narrows tight junctions in jejunum at diarrhoea onset. Serotonin antagonist mildly prevents okadaic acid-caused proximal colon damage. Cyproheptadine ameliorates okadaic acid caused stools' electrolytic profile. Okadaic acid triggers secretory diarrhoea involving serotoninergic pathways.